The influence of the dhuha prayer habituation program on the spiritual quotient of 5-6 year old children - rachmani, zahira indy; hasjiandito, akaat (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background : Spiritual Quotient (SQ) is an essential aspect of early childhood development as it relates to the formation of character and religious values. Aim : This study aims to examine the effect of the Dhuha Prayer Habituation Program on the development of SQ in children aged 5–6 years Method : The research was conducted at TK Pembina Plus Dewi Masyithoh Kalikangkung with a sample of 37 children. A quantitative approach with an ex-post facto design was employed. Data were collected through closed-ended questionnaires, structured observations, and documentation. Instrument validity and reliability were tested using the product moment correlation technique. Data were analyzed using simple linear regression with the aid of SPSS. Result : The results showed a significant influence between the Dhuha prayer habituation program and children’s SQ, with a coefficient of determination (R²) value of 0.500 or a contribution of 50%. Some SQ indicators developed optimally, while others were still in the early stages of development. Conclusion : This study offers a scientific contribution through direct quantitative measurement of the impact of religious habituation on SQ, a topic that has rarely been explored in detail. The practical implication of these findings highlights the importance of integrating religious activities into the PAUD curriculum as a strategy for fostering children's spiritual character from an early age.